PENGARUH KEPERCAYAAN, HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN BELANJA ONLINE DI MARKETPLACE SHOPEE SURABAYA - Winata, Imelda Sharon (Seminar Nasional Ilmu Terapan, 2024)
The rapid development of the times affects the development of technology as well. The increasingly advanced technology also helps facilitate everything, including shopping. The rise of online marketplace development in Indonesia, starting from Tokopedia, Bukalapak, BliBli, OLX, and also Shopee has provided convenience for many people. But behind this positive side, of course, there is a negative side to the development of this marketplace. In this study, researchers are looking for the effect of trust, price, and service quality on online shopping customer satisfaction in the Shopee Surabaya marketplace. This study has a period of 2023 to 2024 by taking a population of all Surabaya people and a sample of 78 people. This study uses quantitative causality methods, and the results of this study found that trust has a significant effect on customer satisfaction. Price has a significant effect on customer satisfaction. Service Quality has a significant effect on customer satisfaction. And simultaneously trust, price, and service quality affect customer satisfaction shopping online at the Shopee Surabaya marketplace.